Design and Application SCR Trigger Circuit for Three-phase Half-wave Controlled Rectifier with Resistive Load - Effendi; Fitriady (LPPM Politeknik Aceh Selatan, 2023)
Power electronics is a field of science that studies and discusses electronics applications related to large-power electrical equipment, one of the sub-subject studied is the AC to DC converter such as a three-phase half-wave controlled rectifier with a resistive load in which output voltage can be controlled by adjusting the triggering delay angle of gate SCR. The components used include a three-phase step-down transformer where the output is used as a reference signal to determine the starting point (30o) and the endpoint (150o) of triggering delay angle, it is also used as a power source for the system, LM393 is used as a comparator between three-phase rectifier (Vd) with DC voltage (Vreference), likewise to compare triangular waves with DC voltages that resulting from changes in the voltage on the potentiometer in order to control the triggering delay angle (α) of SCR. The first step that must be taken to make measurements using an oscilloscope is to determine the ton and toff values for each angle by rotating the potentiometer on the comparator circuit and then measuring the average output voltage (Vo), determination the triggering angle in this research is still done manually so that the measurement results compared to the calculation has a difference this is due to the level of accuracy in observing the oscilloscope, on the other hand, the three-phase transformer and sources used are not in ideal conditions.